Forming the Mindset of Gender Equality in Students as a Socio-Pedagogical Problem - qizi, Allayarova Naila Yakshonor (International Journal on Integrated Education, 2023)
the article is devoted to the identification, analysis, and actual issues in pedagogy of the pedagogical conditions for the formation of gender equality thinking among students today.